Narrow-Linewidth Laser Linewidth Measurement Technology - Bai, Zhenxu; Zhao, Zhongan; Qi, Yaoyao; Ding, Jie; Li, Sensen; Yan, Xiusheng; Wang, Yulei; Lu, Zhiwei (Frontiers in Physics, 2021)
A narrow-linewidth laser with excellent temporal coherence is an important light source for microphysics, space detection, and high-precision measurement. An ultranarrow-linewidth output with a linewidth as narrow as subhertz has been generated with a theoretical coherence length over millions of kilometers. Traditional grating spectrum measurement technology has a wide wavelength scanning range and an extended dynamic range, but the spectral resolution can only reach the gigahertz level. The spectral resolution of a high-precision Fabry–Pérot interferometer can only reach the megahertz level. With the continuous improvement of laser coherence, the requirements for laser linewidth measurement technology are increasing, which also promotes the rapid development of narrow-linewidth lasers and their applications. In this article, narrow-linewidth measurement methods and their research progress are reviewed to provide a reference for researchers engaged in the development, measurement, and applications of narrow-linewidth lasers.